Repeatability and Agreement of a Swept-Source Optical Coherence Tomography–Based Biometer IOLMaster 700 Versus a Scheimpflug Imaging–Based Biometer AL-Scan in Cataract Patients. Issue 1 (January 2020) - Chan, Tommy C.Y.; Wan, Kelvin H.; Tang, Fang Yao; Wang, Yu Meng; Yu, Marco; Cheung, Carol
Abstract : Purpose: To compare the repeatability and agreement between a swept-source biometer and a Scheimpflug biometer in cataract patients. Methods: Three consecutive measurements were obtained using a swept-source biometer (IOLMaster 700) and a Scheimpflug biometer (AL-Scan) in 52 eyes of 52 patients. Keratometry, central corneal thickness (CCT), anterior chamber depth (ACD), axial length, and white-to-white (WTW) distance were recorded. Astigmatism values were transformed into vector components of J0 and J45. Intraoperator repeatability was analyzed using intraclass correlation coefficients (ICCs) and reproducibility coefficients (RCs). Agreement of measurements between the two devices was evaluated using the Bland–Altman method. Results: The IOLMaster 700 showed higher ICCs and lower RCs for the mean keratometry (Km) ( P ⩽0.018), CCT ( P ⩽0.027), and ACD ( P ⩽0.001) measurements, whereas the AL-Scan showed higher ICC and lower RC for the J45 vector component of astigmatism at the 2.4-mm zone ( P ⩽0.034). Both the devices had excellent repeatability (ICC=0.999) in axial length measurement. Systematic differences were found in Km, CCT, ACD, and WTW ( P ⩽0.018) between the devices. The mean difference for Km was −0.196 and −0.144 D measured at the 2.4-mm zone and 3.3-mm zone, respectively. The corresponding mean difference for CCT, ACD, and WTW distance was 14.92 μm, −0.017 mm, and 0.283 mm, respectively. These differences led to a statistically significant but clinically insignificant difference in the prediction of intraocular lens power. Conclusions: This study showed significant differences in anterior segment measurement repeatability and agreement between a swept-source biometer and a Scheimpflug biometer in eyes with cataract.